2017
DOI: 10.1016/j.jhsa.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Comparison of Outcomes Following Simple Syndactyly Reconstruction With Skin Grafts or a Dorsal Metacarpal Advancement Flap

Abstract: Therapeutic IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
1
30
0
1
Order By: Relevance
“…Performing an objective assessment of scar quality after surgery can be challenging. Many researchers have only reported ‘acceptable’ (Ekerot, 1999) scar quality and ‘good cosmesis’ (De Smet et al., 1998), which are difficult to interpret and compare (Sullivan and Adkinson, 2017). Although various scar scales are available, only a few studies of syndactyly have made use of them (Lumenta et al., 2010; Sulser et al., 2016; Widerberg et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing an objective assessment of scar quality after surgery can be challenging. Many researchers have only reported ‘acceptable’ (Ekerot, 1999) scar quality and ‘good cosmesis’ (De Smet et al., 1998), which are difficult to interpret and compare (Sullivan and Adkinson, 2017). Although various scar scales are available, only a few studies of syndactyly have made use of them (Lumenta et al., 2010; Sulser et al., 2016; Widerberg et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing skin graft techniques to graft-less techniques, the latter have been found to cause fewer complications and prevent the need for additional procedures (Magdi Sherif, 1998; Sullivan and Adkinson, 2017; Sykes and Percival, 1989). Sullivan and Adkinson (2017) performed a systematic review comparing complications and results between skin grafts and the dorsal metacarpal advancement flap. They found a significantly higher incidence of web creep in the skin graft group ( p ≤ 0.05).…”
Section: Introductionmentioning
confidence: 99%
“…Web creep is the most common complication after syndactyly release usually appearing within 3 years after surgery, with a reported incidence of up to 60%. 3 , 14 , 28 Postoperative infections and partial skin graft loss can lead to web creep, in which risk appears to vary also between different web reconstruction techniques. 25 , 27 , 28 Age at the time of surgery does not seem to correlate with the risk of web creep, 25 , 27 which seems to be similar in patients treated with (4%–30%) or without (3%–24%) skin grafts.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Previous studies have shown that skin grafts increase the risk of web creep by exerting tension across the web space, particularly when the graft abuts either the dorsal commissure flap or palmar scar junction. [12] Of the surgical techniques reviewed, those described by Matsumine et al [11] in 2011, Hsu et al [14] in 2010 and Yamashita et al [8] in 2016 do not require the use of a skin graft for the flap donor site.…”
Section: Discussionmentioning
confidence: 99%